Nowy model konsumpcji treści telewizyjnych – użytkownik zdobywa przewagę nad oferentem telewizji - Monika Mizielińska-Chmielewska (Studia i Materiały)
The new media technologies offered more possibilities to the user and equipped him with the instruments to takeover the control or establish the dialogue with the broadcaster. The viewer becomes the editor of his own TV program. This article presents above trends on the basis of reports of regulating authority for the broadcasting and telecommunications of the United Kingdom-OFCOM in comparison with the preferences of Polish consumer, defined on the basis of author’s research, conducted within the doctoral thesis at the Faculty of Management at Warsaw University, under the supervision of Prof. UW dr hab. Krzysztof Klincewicz. The research was carried out in 2012, using the method of expert interviews and the survey research of 1298 television and the Internet users in Poland. The objective of the study was defining the preferences and degree of innovativeness of potential users of interactive television. Both, OFCOM study and research of the author, confirm the thesis of progressing change in consumption patterns of television content. Viewers, equipped with Smart TVs, laptops, tablets and smartphones are expecting to get the content anytime.